The Influence of Technostress on Cyberslacking Among Emerging Adults University Students: An Indonesian Context - Vania Ardelia (Epistema, 2023)
The rapid development of technology implementation in the educational processes has brought benefits and challenges, especially for university students. These challenges would then cause students to experience technostress, which might lead to cyberslacking behavior in the classroom. Meanwhile, study on technostress and cyberslacking still needs to be expanded, especially among emerging adults. The emerging adult developmental stage requires tasks that could also lead to stress. Therefore, this research aimed to investigate the influence of technostress on cyberslacking among emerging adult university students. The current study surveyed 121 emerging adult university students using an online questionnaire. Participants completed the demographic scale, the Technostress scale, and the Cyberslacking scale. Data were analyzed using the Structural Equation Modelling (SEM) technique. Results showed a slight trend toward the significance of technostress in predicting cyberslacking behavior among emerging adult university students. Nevertheless, this study contributes to the currently limited studies on technostress and cyberslacking. Further suggestions include operationalizing the technostress definition and involving additional possible mediator variables.